Peran Guru Dalam Penanaman Sikap Anti Bullying Verbal Dalam Pembelajaran PKN di Sekolah Dasar - Fadil, Khaidir (Institut Agama Islam Daruttaqwa Gresik, 2023)
This study aims to determine, (1) Strategies for preventing verbal bullying behavior at SDIT Kemuning through Civics Education, (2) factors that influence the occurrence of verbal bullying behavior at SDIT Kemuning. (3) The role of teachers in instilling anti-bullying attitudes at SDIT Kemuning through Civics learning. (4). The impact of verbal bullying on students at SDIT Kemuning. This research is a qualitative study using descriptive methods to find out the role of teachers in instilling anti-verbal bullying attitudes at SDIT Kemuning through Civics Learning. The research subjects in the research school were SDIT Kemuning teachers, who implemented the learning process of the learning process using the 2013 Curriculum which implemented Character Education in Learning. This research uses an indirect interview method. The primary data source used was the Civics subject teacher. Secondary data in the form of journals and books. The data collection techniques used are observation and interviews. The data analysis technique uses the interaction model analysis technique according to Miles and Huberman, namely data reduction, data presentation (data visualization) and conclusion drawing (verification). The results showed that the strategy of preventing Verbal bullying behavior through Civics learning in students at SDIT Kemuning is by calling the two problematic students and then talking to them after that they are advised and given direction. Then, the supporting factor for bullying behavior at the SDIT Kemuning level is because students often do not realize that what they do, such as mocking, includes verbal bullying. Then, the role of teachers in instilling anti-bullying attitudes is to provide advice to students both individually and classically to all students. building awareness and understanding of bullying and its effects to all parties, especially students, working with parents, filling positive activities, and forms of cooperation that can involve students such as duha prayers, murojaah activities to instill character, collaborating with subject teachers to carry out supervision.